1997
DOI: 10.1029/97gl03096
|View full text |Cite
|
Sign up to set email alerts
|

Array tracking of the volcanic tremor source at Deception Island, Antarctica

Abstract: Abstract. We have found experimental evidence which shows that the volcanic tremor recorded at Deception Island (South Shetland Islands, Antarctica) is a superposition in time of overlapping hybrid events. We studied data from a small aperture seismic array. Data analysis for tremor and hybrids included: (1) spectral analysis; (2) apparent slowness and back-azimuth determination by using the zero-lag cross-correlation method; and (3) polarization analysis. Both types of events share these common features: (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 16 publications
2
53
0
5
Order By: Relevance
“…Injection of water into hot dry rock has been found to produce seismic signals similar to low-frequency volcanic earthquakes and supports the idea of a source that involves the opening of tensile cracks caused by excess £uid pressure (Bame and Fehler, 1986). The overall similarity of tremor and low-frequency events in the time and frequency domains, notwithstanding their di¡erent signal duration, has been pointed out by many authors as indicating that a common source may be at work, and which of the two seismic signals will be generated depends on the duration of the excitation mechanism (Fehler, 1983;Chouet, 1985;Hofstetter and Malone, 1986;Tsuruga et al, 1997;Almendros et al, 1997).…”
Section: Excitation Of £Uid-¢lled Cracksmentioning
confidence: 78%
See 1 more Smart Citation
“…Injection of water into hot dry rock has been found to produce seismic signals similar to low-frequency volcanic earthquakes and supports the idea of a source that involves the opening of tensile cracks caused by excess £uid pressure (Bame and Fehler, 1986). The overall similarity of tremor and low-frequency events in the time and frequency domains, notwithstanding their di¡erent signal duration, has been pointed out by many authors as indicating that a common source may be at work, and which of the two seismic signals will be generated depends on the duration of the excitation mechanism (Fehler, 1983;Chouet, 1985;Hofstetter and Malone, 1986;Tsuruga et al, 1997;Almendros et al, 1997).…”
Section: Excitation Of £Uid-¢lled Cracksmentioning
confidence: 78%
“…EtnaEreditato and Luongo, 1994;Wegler and Seidl, 1997) and is strongly in£uenced by path e¡ects. There are also a few studies that indicate a mixed composition of the wave¢eld with the presence of both body and surface waves (Deception Island, Almendros et al, 1997). Other studies utilised data from local arrays, by using the polarisation properties of the wave¢eld in order to calculate the backazimuth of the propagating waves and estimate the location of the source (Kilauea-Ferrazzini et al, 1991;Masaya-Me ¤taxian et al, 1997).…”
Section: The Nature Of Volcanic Tremormentioning
confidence: 99%
“…Deception Island is an active volcanic complex in the Antarctic Peninsula (Almendros, Ibanez, Alguacil, DelPezzo, & Ortiz, 1997;Rey, Somoza, & Martinez Frias, 1995). Geochemical analysis of caldera seafloor sediment shows a dominance of andesitic lava, rich in aluminum silicate (Baker, Davies, & Roobol, 1969;Rey et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Geophysical investigations since 1987 have indicated that seismic activity on Deception Island is characterized by volcano-tectonic earthquakes, long-period and hybrid events, and tremor (Vila et al 1992;Almendros et al 1997). The 1969 seismogram and contemporary observations suggest that tremor and volcano-tectonic earthquakes were both involved in the activity (below), although the harmonic signature of very small volcano-tectonic earthquakes is not always separable in the comparatively crude record.…”
Section: Seismicitymentioning
confidence: 94%
“…It is likely that both seawater and freshwater infiltrate the volcanic edifice and continuously replenish aquifers on the island (Vila et al 1992). For example, the incidence of tremor is roughly correlated with days on which there was rapid snow melt (Almendros et al 1997;Villegas et al 1997). Corrieg et al (1997) related tremor to vaporization of groundwater at depths of 2-3 km.…”
Section: Seismicitymentioning
confidence: 96%